Arctic Site Survey - Chow, T S (1972)
The report discusses the development of a ray tracing program for calculating the sound intensity from sources in the ocean with surface and bottom reflections. Salinity and temperature gradients have been taken into consideration to calculate the sound velocity and absorption loss. The sound intensity is calculated by energy considerations included in the ray tube of adjacent rays. A formula has also been developed for calculating the intensity along a ray without considering the variation in the ray tube area. This involves the calculation of the radius of curvature of the wave front along the ray. Future plans on ray tracing call for the development of techniques for calculating sound intensities in the caustic region and higher order corrections. Sponsored in part by DARPA.